Taking charge at work: the mediating role of role breadth self-efficacy - Ngo, Michelle She Min (2022)
This study examines the motivational process of taking charge among the general working population. Specifically, this study attempts to investigate the impact of proactive personality and co-worker support on taking charge. In addition, this study recognises the significance of proactive motivational states in stimulating proactive goal regulation and striving. By incorporating role breadth self-efficacy (RBSE) to represent the can-do motivational state, this study also seeks to understand whether RBSE mediates the relationships between the antecedents and taking charge. The hypothesised model was tested using mediation analysis on a sample of 193 individuals, mainly working in Malaysia’s organisations and holding different positions. The findings show that proactive personality and co-worker support were significantly and positively related to taking charge. Moreover, the study confirms that RBSE mediates the relationships between proactive personality and taking charge and co-worker support and taking charge. The paper represents one of the few attempts to study the effects of both proactive personality and co-worker support on taking charge. Distinctly, the study confirms employees’ personalities as a more significant determinant of taking charge than co-worker support among the samples. Likewise, by confirming the mediation effects of RBSE, the findings further imply that practitioners should make an effort to enhance employees’ RBSE to develop taking charge, which is helpful to ensure organisational sustainability.